Selenium Linked to Increased Antioxidant Levels and Decreased Free Radicals in Lung Tissue of Wistar Rats Exposed to E-Cigarette Smoke - Bambang Wirjatmadi (Journal of Global Pharma Technology, 2020)
Objective: This study aimed to find out whether selenium could increase levels of antioxidants and decrease free radicals in lung tissue of Wistar rats after exposure to e-cigarette smoke. Methods: This study used an experimental method with control group design. Male Wistar rats with criteria aged 2–3 months, weighing 200-250 grams were used as animal models in this study to assess cell damage through the expression of Superoxide Dismutase, Glutathione Peroxidase and Malondialdehyde in the lung tissue using immunohistochemical staining. E-cigarette smoke containing 6 mg of nicotine was given to each group of animal models with differences in the amount and duration of time. The adaptation process in experimental animals was carried out for approximately 5 days. Results and Conclusion: Selenium has been shown to increase the expression of antioxidant superoxide dismutase and glutathione peroxidase, and decrease the levels of malondialdehyde in cells following oral administration of selenium in Wistar rats (p <0.05). In addition, selenium also reduced the amount of free radical in the cells; when it was given before exposed to e-cigarette smoke. It can be concluded that oral selenium can increase antioxidants levels and decrease free radicals in lung tissue cells due to exposure to e-cigarette.